Investigation of transient performance of capacitor voltage transformer (CVT) - Mekhilef, Saad; Cheng, Hock Lim; Bakar, Ab Halim Abu (2008)
This paper reports the digital-time domain studies on a typical 132kV Capacitor Voltage Transformer (CVT) model. The transient studies are conducted using Alternative Transient Program (ATP-EMTP). Simulation results corresponding to the CVT transient response under both system fault and ferroresonance condition are reported in this paper. Transient studies are performed (1) to identify the CVT components that contribute to the transient response of CVT, (2) to determine system condition that affect the CVT transient response. A lightning simulation case study is also presented to demonstrate the ferroresonance oscillation sustained inside a CVT due to lightning strike as affected by the factors of lightning current amplitude and distance between CVT and lightning arrester.